DESCRIPTION OF EXAMINATION OF BLOOD SUGAR LEVELS IN CATARACTS IN TOTO KABILA HOSPITAL IN 2022 - Katili, Putri Regita; Marlia; D. Soga, Gayatri (LPPM Universitas Bina Mandiri Gorontalo, 2024)
Blood sugar is a metabolic disorder in which an inability to oxidize carbohydrates is found due to disturbances in the normal insulin mechanism. People with diabetes mellitus will usually have blood sugar levels that are higher than normal people. A rapid increase in blood sugar can cause acute lens swelling and pseudomyopia, but this phenomenon is reversible. One of the complications of diabetes mellitus is chronic microvascular complications that can attack the eyes. As for goalsof this study is to find out the results of an examination of the description of blood sugar levels when in patients with cataracts at Toto Kabila Hospital in 2022. The method in this study used a descriptive quantitative approach and a purposive sampling technique by determining certain criteria or considerations. The results showed that of the 30 samples, consisting of 11 male respondents and 19 female respondents, the average age of the respondents was 45 years to 85 years, there were 13 normal blood sugar levels or (43.3%) and blood sugar levels abnormal blood as much as 17 or (56.7%)